Cytoplasmic expression of a model antigen with M Cell-Targeting moiety in lactic acid bacteria and implication of the mechanism as a mucosal vaccine via oral route. Issue 30 (5th July 2021) - Oh, Seo-Ho; Kim, Sung-Hee; Jeon, Ji-Hye; Kim, Eun Bae; Lee, Nam-Kyung; Beck, Samuel; Choi, Yun-Jaie; Kang, Sang-Kee
Highlights: Cytoplasmic antigen in LAB could sufficiently induce antigen-specific immunogenicity. Spontaneous release of cytoplasmic antigen from LAB is crucial for vaccine efficacy. Antigen expression level matters rather than its localization for LAB vaccine design. M cell targeting moiety could improve immunogenicity of an antigen in oral vaccine. Abstract: Lactic acid bacteria (LAB) have been widely studied as mucosal vaccine delivery carriers against many infectious diseases for heterologous expression of protein antigens. There are three antigen expression strategies for LAB: cytoplasmic expression (CE), cell surface display (SD), and extracellular secretion (ES). Despite the generally higher protein expression level and many observations of antigen-specific immunogenicity in CE, its application as a mucosal vaccine has been overlooked relative to SD and ES because of the antigens enclosed by the LAB cell wall. We hypothesized that the antigens in CE could be released from the LAB into the intestinal lumen before host bacterial access to gut-associated lymphoid tissue (GALT), which could contribute to antigen-specific immune responses after oral administration. To elucidate this hypothesis, three recombinant Lactobacillus plantarum (LP) strains were constructed to produce a model antigen, BmpB, with or without an M cell-targeting moiety, and their immunogenicities were analyzed comparatively as oral vaccines in mouse model. The data indicated that the recombinant LPs producing BmpBs with different conformations could induce mucosal immunity differentially. This suggests that the cytoplasmic antigens in LAB could be released into the intestinal lumen, subsequently translocated through M cells, and stimulate the GALT to generate antigen-specific immune responses. Therefore, the CE strategy has great potential, especially in the application of oral LAB vaccines as well as SD and ES strategies. This research provides a better understanding of the mechanism for recombinant oral LAB vaccines and gives insight to the future design of LAB vaccines and oral delivery applications for useful therapeutic proteins.